Techno-economic and environmental assessment of battery integrated wind farm siting across offshore Nigeria - Akporhonor, Gbubemi Kevin (Taylor & Francis, 2025)
This study investigates the economic, technical, and environmental impacts of integrating a battery energy storage system (BESS) with an offshore wind farm near Koko Sea Port, Nigeria. As renewable energy curtailment increases and Nigeria’s energy demand grows, energy storage systems (ESS) are essential for ensuring a firm power supply. While offshore wind farms have advanced globally, Nigeria remains underrepresented in related research. This study addresses this gap by presenting a comprehensive techno-economic and environmental assessment (TEEA) of an ESS-integrated wind farm along Nigeria's coast. The system includes 477 Siemens Gamesa SG 2.1-114 turbines, producing 930 GWh annually with an instantaneous output of 0.35 GW. Vanadium Redox Flow Batteries (VRFB) were identified as the most suitable ESS, providing 528 MWh of storage to maintain power during wind variability. Economic analysis indicates a Levelised Cost of Energy (LCOE) of 393.35 $/MWh, comparable to global 2020 benchmarks for newly commissioned offshore wind farms. Environmental analysis reveals significant carbon savings, with emissions reduced by over 107% and 74% relative to coal and gas power plants. This study highlights the potential of battery-integrated offshore wind farms to advance Nigeria’s clean energy transition, offering insights for policymakers and stakeholders pursuing sustainable development and Paris Agreement commitments.
Keywords: Offshore wind farm; energy storage system; vanadium redox flow battery; techno-economic and environmental assessment; multiple-criteria decision-making; carbon savings